Probability and Impact of Risk on the Palm Sugar Household Industry in Air Periukan Sub-District Seluma District - Herri Fariadi Lubis; Satria Putra Utama; Indra Cahyadinata (UNIVED Press, Dehasen University Bengkulu, 2023)
Risk is significant since it is an unforeseeable event that causes problems for palm sugar business participants. To establish good corporate governance, risk management is required. The goal of this study is to identify risk sources, estimate risk likelihood, and assess risk impact on the palm sugar home industry in Air Periukan District, Seluma Regency. The quantitative and qualitative research methodologies employed include descriptive analysis, z-score, and VaR (Value at Risk). The findings revealed that the sources of risk in the palm sugar home industry in Air Periukan District, Seluma Regency were at production risk, specifically low palm sugar production, and at social risk specifically teens consuming palm sap as palm wine. The likelihood value of production risk in the palm sugar home industry in Air Periukan District is 53.27%, while the social risk of youths using palm sap as a palm wine drink is 26.33%. The effect value of low-risk palm sugar production is Rp. 531,703.164 per production, and the social risk impact value of teens who use palm sugar as palm wine is Rp. 47,173.152 per production.